2018
DOI: 10.1109/tvcg.2018.2794658
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of Self-Contact for Embodiment in Virtual Reality

Abstract: With the broad range of motion capture devices available on the market, it is now commonplace to directly control the limb movement of an avatar during immersion in a virtual environment. Here, we study how the subjective experience of embodying a full-body controlled avatar is influenced by motor alteration and self-contact mismatches. Self-contact is in particular a strong source of passive haptic feedback and we assume it to bring a clear benefit in terms of embodiment. For evaluating this hypothesis, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 34 publications
2
33
0
1
Order By: Relevance
“…A correct representation of self-contact appears to support a strong sense of embodying an avatar during immersion in VR (Bovet et al, 2018). Another study found a significant shape by texture interaction: a natural skin texture increased the strength of the RHI for a hand-shaped object, but not for a nonhand-shaped object (Haans et al, 2008).…”
Section: Visual Realism (Similarity)mentioning
confidence: 91%
“…A correct representation of self-contact appears to support a strong sense of embodying an avatar during immersion in VR (Bovet et al, 2018). Another study found a significant shape by texture interaction: a natural skin texture increased the strength of the RHI for a hand-shaped object, but not for a nonhand-shaped object (Haans et al, 2008).…”
Section: Visual Realism (Similarity)mentioning
confidence: 91%
“…Natural touch sensation would not only improve the overall experience, but could further enhance learning of simple (Bark et al, 2015) as well as complex motor behavior (Sigrist et al, 2015). This is especially true when combined with VR-based training scenarios that are currently often lacking tactile feedback as well (Weiss et al, 2006; Bovet et al, 2018).…”
Section: Applications In Assistive Roboticsmentioning
confidence: 99%
“…Moreover, this kind of touch has been shown to increase body ownership (Hara et al, 2015) and first preliminary studies have extended such scenarios to rather complex situations of self-touch (Dieguez et al, 2009; Huynh et al, 2018). Research on embodiment in VR also shows that correct self-contact is more important for the feeling of embodiment than the mapping of movements (Bovet et al, 2018). Yet, tactile feedback is often limited to the hand or body parts, which was shown to constrain the implementation of passive self-touch in VR (Bovet et al, 2018).…”
Section: Applications In Assistive Roboticsmentioning
confidence: 99%
“…Embodiment is defined as the "subjective experience of using and 'having' a Journal of Software Engineering and Applications body" [18] [24]. This is formally defined as follows: where E is some alternative representation of a body, "E is embodied if some properties of E are processed in the same way as the properties of one's body" [24] [25]. To achieve this experience, Kilteni et al suggest three components that influence the embodiment experience [18]: sense of self-location, agency, and body ownership.…”
Section: Copresence and Embodimentmentioning
confidence: 99%